The administrative problems of the diocesan secondary schools of Nueva Segovia - Lazo, Peregrino R. 1939- (s.n.], 1969)
The study determined the major administrative problems of the diocesan secondary schools of Nueva Segovia with the aim of identifying these major problems and their causes and to give recommendations for their solutions. The normative survey technique was used with the questionnaire as the principal instrument for data gathering.